SO YOU ARE ASKING TO GO HOME? RESIDENT PERCEPTIONS OF TRANSITIONING FROM SKILLED NURSING FACILITIES TO COMMUNITY. (11th November 2018) - Galambos, C; Park, G; Popejoy, L L
Abstract: It is estimated that 23% of Medicare patients discharged from skilled nursing facilities (SNF's) are re-hospitalized within 30 days. (Mor, Intrator, Feng, Grabowski, 2010). Improvements to SNF discharges are needed to avoid unnecessary transfers. This qualitative study explored older people's concerns about transitions to home prior to their discharge, and was part of a larger research project that implemented Project Reengineered Discharge to improve the care transitions process in SNF's. Ten short stay residents from two skilled nursing facilities were interviewed to understand the pending transition to home from their perspective. Using a constant comparative method two researchers conducted independent coding and met as a group to identify emerging themes. Rising themes included (1) care/assistance; (2) social supports/ care networks; (3) physical environment/ finances; and (4) discharge communication. The results will be presented along with recommendations to address needs and gaps in services that emerged from these interviews.